2022
DOI: 10.1186/s40494-022-00731-4
|View full text |Cite
|
Sign up to set email alerts
|

A multi-analytical approach to identify red colorants on woodblock prints attributed to Suzuki Harunobu

Abstract: Red organic dye identification is an important topic for conservation of Japanese ukiyo-e prints. Of particular interest are the works of Suzuki Harunobu, who was working at the inception of full-color printmaking. These prints were made on thin kōzo paper and woodblock printed with semi-transparent to opaque regions of dye(s) and/or pigment(s) mixed with binder. This study used imaging analysis, X-ray fluorescence (XRF), Raman, and surface-enhanced Raman spectroscopies (SERS) to identify the red dyes and pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Since the risk of damaging the appearance of this type of objects can be very high, they are considered too fragile to allow sampling and noninvasive techniques are preferred for their investigation. As far as we know, only a few studies involving destructive techniques have been reported, namely liquid chromatography with mass spectrometry (HPLC-MS) and surface-enhanced Raman spectroscopy (SERS) [4,8]. As a consequence, imaging and spectroscopic techniques are the most adopted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the risk of damaging the appearance of this type of objects can be very high, they are considered too fragile to allow sampling and noninvasive techniques are preferred for their investigation. As far as we know, only a few studies involving destructive techniques have been reported, namely liquid chromatography with mass spectrometry (HPLC-MS) and surface-enhanced Raman spectroscopy (SERS) [4,8]. As a consequence, imaging and spectroscopic techniques are the most adopted.…”
Section: Introductionmentioning
confidence: 99%
“…The most common coupling is with fiber-optic reflectance spectroscopy (FORS) and/or X-ray fluorescence (XRF) [3,4,[9][10][11][12][13], although also the combined use of spectrofluorimetry has been reported [14,15]. Moreover, again referring to single-point spectroscopic methods, the application of Fourier-transform infrared (FTIR) [3,15,16] and Raman spectroscopy [4,8,17] was also documented for the study of woodblock prints. It is worth noting that these latter techniques have the great advantage of providing more specific information on the analytes as they are vibrational spectroscopies.…”
Section: Introductionmentioning
confidence: 99%